10x+9(3)=8

Simple and best practice solution for 10x+9(3)=8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10x+9(3)=8 equation:


Simplifying
10x + 9(3) = 8

Multiply 9 * 3
10x + 27 = 8

Reorder the terms:
27 + 10x = 8

Solving
27 + 10x = 8

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-27' to each side of the equation.
27 + -27 + 10x = 8 + -27

Combine like terms: 27 + -27 = 0
0 + 10x = 8 + -27
10x = 8 + -27

Combine like terms: 8 + -27 = -19
10x = -19

Divide each side by '10'.
x = -1.9

Simplifying
x = -1.9

See similar equations:

| 1/4d_ | | f(x)=ln(81sin^2x) | | 3+4x=13+9x | | 2a^3b^0/c^2)-3 | | An=n^2+3n | | Tan^2x-5tanx-6=0 | | 2y=-3x+8 | | -4(7x+1)=-312 | | -5=-20+-25 | | 12x^2-132x+252=0 | | 30=7+N-4+8 | | 40=-2(23-y)+3(y-3) | | -8=17+6z | | 6(x+6)=-9+3x | | 7=3(23-x)+2(x-2) | | 7=t^2-6t | | -3p-48=0 | | 3r+11=2-3(3r+3) | | -7+x=-3x+25 | | 3ln(5x+4)=22 | | 4(4x-9)-6=4(x-4)+46 | | 16x^2-7t=17t-9 | | 36-6x=14+5x | | 2u^2+13u+15=0 | | (4x^2)+4x+(4y^2)-32y-335=0 | | 4x^2-147=0 | | (7/2)^-1=-1/7x | | (X-7)/2=(5-x)/4 | | 54-8x=18+10X | | 3(3x+5)=60 | | 8(3t-5)+12=-8 | | 54-8x=18+10 |

Equations solver categories